Chain dynamics and glass transition of dry native cellulose solutions in ionic liquids. Issue 1 (27th November 2019) - Utomo, Nyalaliska W.; Saifuddin, Indira; Nazari, Behzad; Jain, Preet; Colby, Ralph H.
Abstract : Glass transition temperatures of cellulose solutions in three ionic liquids, determined from the peak in tan( δ ) = G ′′/ G ′, exhibit a minimum at about 2 wt% cellulose. Abstract : Dry native cellulose solutions in 1-butyl-3-methylimidazolium methylphosphonate (EMImMPO3 H), 1-butyl-3-methylimidazolium acetate (EMImAc), and 1-butyl-3-methylimidazolium chloride (BMImCl) ionic liquids (IL) were investigated using subambient linear viscoelastic oscillatory shear. Glass transition temperatures ( T g ) of solutions with various cellulose concentrations up to 8.0 wt% were observed as the peaks of loss tangent tan( δ ) and loss modulus G ′′ in descending temperature sweeps at 1 rad s −1 . Cellulose/IL solutions showed a minimum in T g at ∼2.0 wt% cellulose content before increasing with cellulose concentration, suggesting a perturbation of the strongly structured IL solvents by the cellulose chains. Isothermal frequency sweeps in the vicinity of T g were used to construct time–temperature-superposition master curves. The angular frequency shift factor a T as a function of temperature indicates Arrhenius behavior within a 9 K range near T g, allowing calculation of fragility, which was found to be constant up to 8.0 wt% cellulose concentration. This result implied that increasing cellulose concentration initially decreases T g due to disrupted ionic regularity of ILs, but does not seem to change their fragility.